Some issues of securing claims arising from corporate legal relations (Journal of actual problems of jurisprudence, 2023)
Issues of corporate relations and corporate governance are topical in the development of the country's economy. As President of the Republic of Kazakhstan K. Tokayev noted in his messages, dozens of national holdings, thousands of state-owned enterprises, and quasi-state organizations operate in the country. However, there is a question about the results and quality of their work, and only in one or two cases is the corporate governance system up to par. This suggests that in other organizations it is necessary to develop a corporate governance system. Its place in the economy is important, because due to the lack of an international corporate governance system of the appropriate level, enterprises and organizations cannot raise funds through the stock exchange.In the article, the author gives the scientific concept of "corporation", "corporate disputes", analyzes the short stories of substantive civil law on the definition of new categories of corporate disputes, their occurrence, legal entities. Suggests ways to identify actual problems related to the definition of departmental subordination of corporate disputes, namely the contradictions of departmental subordination and understanding the reasons that caused them, and their resolution. Emphasizes the features of substantive and procedural law in relation to corporate disputes. In addition, during the transitional period of the economy of Kazakhstan, changes and additions are made to some sections of the law «On a joint-stock company», which provides an effective form of management and business of a joint-stock company.Key words: corporation, corporate dispute, joint-stock company, legal entity, shares, corporate relations, dividends, earnings per share, share market price, court, lawsuit.